Reduction in vehicle operating costs with the introduction of a public transit central terminal in the central business district of Manila - Genuino, Ernesto S. (1981)
This paper discusses the desirability of providing a Public Transit Central Terminal (PTCT) in the Central Business District (CBD) of Manila, together with the attendant considerations in the establishment pf such complex facility. An attempt is also made to estimate the reduction of vehicle operating costs which can be anticipated as a direct benefit from the provision of the PTCT due to the removal of loading and unloading activities from the streets of the CBD which activities will be transferred to the PTCT where they properly belong. This calculation is based on traffic, travel time and delay data, and vehicle characteristics taken from the Metro Manila Traffic Engineering and Management (TEAM) Project of the Ministry of Public Highways (MPH) while data on the cost of congestion are taken from the Transportation and Traffic Engineering Handbook of the Institute of Traffic Engineering Handbook of the Institute of Traffic Engineers edited by Beerwald, Huber and Keefer, which, in turn, are taken from a study by P.J Claffey, Running Costs of Motor Vehicles as Affected by Road Design and Traffic. These congestion cost data are modified to reflect the vehicle composition and costs of fuel, tires and parts as applicable in the CBD.
The modification assumes that the rates of fuel consumption or tire wear of each type of vehicle during speed change operations are in the same proportion as their rates during continuous operation. The tables in the handbook are supposed to consist of contributions or consumption shares from each type of vehicle on which composition they are based. The relative rates of consumption for each type of vehicle during continuous or uniform operation are then used to determine the rates of consumption of each type of vehicle during slowdown-speed-up or stop-go operations in terms of the handbook's table values. The CBD vehicle composition and local costs are then applied to modify the handbook's set of congestion cost data. With the expectation that congestion in the CBD can only get worse if nothing is done to keep it within an acceptable level measures have to be taken to improve the CBD's accessibility and one of them is the establishment of a PTCT. It is admitted however, that a comprehensive feasibility study must be undertaken first to check on its overall advisability. The calculated reduction in vehicle operating costs due to the removal of loading and unloading activities from the streets of the CBD is a step in this direction and it is deemed substantial enough to merit a closer look at the PTCT's feasibility.
Mimeographed.
Thesis (M.S.)--University of the Philippines, Diliman.
Keywords: Vehicles -- Cost of operation; Terminals (Transportation) -- Philippines -- Manila metropolitan area